English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

look at these steps plz:

ln y = x ln (sin x)

differentiate:
1/y dy/dx = ln (sin x) + x (1/sin x) (cos x)
------how do you go from the above line to the below line?-----
=> dy/dx = (sin x)^x (ln (sin x)) + x (cos x) (sin x)^(x-1)
= (sin x)^(x-1) (sin x ln (sin x) + x cos x)

2007-07-19 19:10:36 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

1/y dy/dx = ln (sin x) + x (1/sin x) (cos x)

cross multiply the y:

dy/dx = y [ ln (sin x) + x (1/sin x) (cos x) ]

now, ln y = x ln (sin x) = ln ({sin x}^x)
this means y = {sin x}^x ..... use that substitution

dy/dx = {sin x}^x [ ln (sin x) + x (1/sin x) (cos x) ]

this is now what you see below the line.
Helped you?


d:

2007-07-19 19:19:13 · answer #1 · answered by Alam Ko Iyan 7 · 0 1

starting with implicit different ion use the operator d/dx( ) to both sides of your equation,thusly:

d/dx( ln y) = d/dx( xln (sinx)
to obtain
dy/dx = yxcos(x) + ysin(x)lnsin(x) where we multiplied both sides by y to solve for dy/dx.

now eleminate y using the oriniginal equation.
you get y =sin(x)^x

now everywhere you see y on the righthandside of the dy/dx equation. substitute this deffinition of y and simplify.

2007-07-20 02:37:00 · answer #2 · answered by william b 2 · 0 0

If you recall you started out with
y = (sin(x))^x
and took to log of both sides to facilitate differentiation:
ln y = xln(sin(x))
You came up with
1/y dy/dx = ln (sin x) + x (1/sin x) (cos x)
which becomes
1/y dy/dx = ln(sin(x)) + xcot(x)
Multiplying both sides by y,
dy/dx = y[ln(sin(x)) + xcot(x)]
substituting the original value of y,
dy/dx = ((sin(x))^x)[ln(sin(x)) + xcot(x)]
The last line is superfluous, but you can arrive at it by multiplying by sin(x)/sin(x):
dy/dx = (((sin(x))^x)/sin(x)) [sin(x)ln(sin(x)) + xsin(x)cot(x)]
(((sin(x))^x)/sin(x)) = (sin(x))^(x - 1) and
sin(x)cot(x) = cos(x), so
dy/dx = ((sin(x))^(x - 1))[sin(x)ln(sin(x)) + xcos(x)]
edit:
dy/dx = (sin x)^x (ln (sin x)) + x (cos x) (sin x)^(x-1)
is correct, but unnecessary, and confuses the issue in my opinion.

2007-07-20 03:04:46 · answer #3 · answered by Helmut 7 · 0 0

becuz, if
ln y = x ln (sin x)
then this means,
ln y = ln ((sin x)^x)
or,
y = (sin x)^x

did u get that?
the general rule is: ln (a^b) = b (ln a)
Now using that, look at your 3rd and 4th lines...

2007-07-20 02:20:49 · answer #4 · answered by ray r 1 · 0 0

NO Idea

2007-07-20 02:13:30 · answer #5 · answered by Anonymous · 0 0

fedest.com, questions and answers